EFFECT OF STORE LAYOUT AND INTERIOR DISPLAY ON CUSTOMER PURCHASING DECISION AT MULTIMART TOMOHON - Boka, Ryalest M. B.; Saerang, David P.E.; Arie, Fitty V. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Today the development of business in this globalization era has increased dramatically. Creative innovation in creating comfortable atmosphere can increase the unity that competes in differentiation strategy and marketing efforts. With rapid business development, in line with the rapid growth of competition. This makes businessman aware of the competitive position of the industry so they must maintain a competitive advantage. This study aims to determine the effect of Store Layout and Interior Display on Customer Purchasing Decision at Multimart Tomohon. This research uses quantitative methods and the total sample is 100 respondents. The results of this study show the effect of Store Layout (X1) on Customer Purchasing Decision (Y) is equal to 0.000 < 0.05 and the value of tcount 3.696 > ttable 1.98472, the effect of Interior Display (X2) on Customer Purchasing Decision (Y) is 0.880 < 0.05 and the value of tcount 5.051 < ttable 1.98472. It means that Store Layout and Interior Display have significant influence on Customer Purchasing Decision and simultaneously all variables in this research have significant influence on Customer Purchasing Decision. Recommendation for Multimart Tomohon is to increase the quality and the convenience of the store layout and interior displays.Keywords: store layout, interior display, customer purchasing decision